2011
DOI: 10.1364/oe.19.019875
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of alkali vapor lasers

Abstract: Detailed numerical analyses are presented of a continuous wave (cw), single spatial mode alkali vapor laser pumped by a diffraction-limited Ti: Sapphire laser. These analyses provide insight into the operation of alkali vapor lasers to aid in the development of high power, diode laser pumped alkali vapor lasers. It is demonstrated that in the laser considered the laser spatial pattern is significantly changed after each pass through the gain medium, and the laser spatial pattern in steady state operation is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The most common techniques, including the Gaussian beam propagation [10,11], the Collins integral [11,12,25], and the BPM [20,21], are based on the combination of the Fresnel integral [34] for free-space propagation with TEA [22] for the component modeling. In the round-trip operator notation this means…”
Section: Paraxial Resonators With Isotropic Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common techniques, including the Gaussian beam propagation [10,11], the Collins integral [11,12,25], and the BPM [20,21], are based on the combination of the Fresnel integral [34] for free-space propagation with TEA [22] for the component modeling. In the round-trip operator notation this means…”
Section: Paraxial Resonators With Isotropic Componentsmentioning
confidence: 99%
“…Therefore they used Kirchhoff's diffraction formula to propagate the field repeatedly along the resonator cavity. Sziklas and Siegman [16,17] already showed that replacing Kirchhoff's diffraction formula by a combination of the angular spectrum of plane waves (SPW) diffraction integral and the thin element approximation (TEA) leads to the beam propagation method (BPM) [18,19], which can be used to simulate resonator cavities containing inhomogeneous complex refractive index distributions, such as thermal lenses and active media [20,21]. However, this approach is also restricted due to the approximative character of TEA.…”
Section: Introductionmentioning
confidence: 99%